Recent Progress and Opportunities for Nucleic Acid Aptamers - Byun, Jonghoe (Life (Basel), 2021)
Coined three decades ago, the term aptamer and directed evolution have now reached their maturity. The concept that nucleic acid could modulate the activity of target protein as ligand emerged from basic science studies of viruses. Aptamers are short nucleic acid sequences capable of specific, high-affinity molecular binding, which allow for therapeutic and diagnostic applications. Compared to traditional antibodies, aptamers have several advantages, including small size, flexible structure, good biocompatibility, and low immunogenicity. In vitro selection method is used to isolate aptamers that are specific for a desired target from a randomized oligonucleotide library. The first aptamer drug, Macugen, was approved by FDA in 2004, which was accompanied by many studies and clinical investigations on various targets and diseases. Despite much promise, most aptamers have failed to meet the requisite safety and efficacy standards in human clinical trials. Amid these setbacks, the emergence of novel technologies and recent advances in aptamer and systematic evolution of ligands by exponential enrichment (SELEX) design are fueling hope in this field. The unique properties of aptamer are gaining renewed interest in an era of COVID-19. The binding performance of an aptamer and reproducibility are still the key issues in tackling current hurdles in clinical translation. A thorough analysis of the aptamer binding under varying conditions and the conformational dynamics is warranted. Here, the challenges and opportunities of aptamers are reviewed with recent progress.